DIALOG INTERAKTIF PROGRAM ACARA GELAR WICARA BUDAYA BERLANDASKAN AGAMA HINDU DI PROGRAMA 4 RRI DENPASAR - I Wayan Sukawinaya; Ni Made Yuliani; I Gusti Ayu Ratna Pramesti Dasih (UHN IGB Sugriwa Denpasar, 2021)
Radio is classified as a fast and punctual mass media because ituses live broadcasts. Initially including one-way mass media, so thatinformation only goes from source to target without any feedback. Thedevelopment of radio as a two-way mass media using the telephone. Radioas an interactive medium provides space for listeners' feedback in theconcept of interactive dialogue. As is done by Program 4 RRI Denpasar inthe Cultural Talk Show program, so that it can be understood thecommunication patterns applied and their functions and implications.Included in qualitative research, the theories used are: cultural normtheory, S-M-C-R (Source-Massage-Channel-Receiver) theory, anddependency theory of mass communication effects.The findings of the study include: that the communication patternapplied to the interactive dialogue program of the Cultural Talk Showprogram based on Hinduism in Program 4 RRI Denpasar is a culturalsegmentation. The broadcast process using linear and circularcommunication patterns is divided into three stages, namely the programstage, the technical stage, and the broadcasting stage. Furthermore, thereare three functions outlined, namely: an educational function, a sociocultural function, and a cultural preservation function based on Hinduism.The implications are very real effects on: cognitive strengthening, affectiveformation, and behavioral development. The concept of interactivedialogue accelerates the feedback process so that feedback is obtainedimmediately and instantaneously.